Risk of Intraatrial Thrombi After Thoracoscopic Ablation in Absence of Heparin and Appendage Closure - Budera, Petr; Osmancik, Pavel; Herman, Dalibor; Talavera, David; Petr, Robert; Straka, Zbynek (The Annals of thoracic surgery, 2017)
BACKGROUND: Catheter and surgical ablation of atrial fibrillation (AF) can be associated with a risk of thromboembolic events. The goal of this study was to assess optimal anticoagulation management during thoracoscopic ablation of AF. METHODS: Fifty-two patients with persistent or long-standing persistent AF underwent hybrid ablation consisting of thoracoscopic ablation followed by electrophysiologic (EP) evaluation and consecutive ablation if indicated. The thoracoscopic ablation was performed using three different anticoagulation protocols: (1) without periprocedural heparin and without occlusion of the left atrial appendage; (2) with periprocedural heparin but without left atrial appendage occlusion; and (3) with periprocedural heparin and left atrial appendage occlusion. Transesophageal echocardiography (TEE) was obligatorily used to screen for intraatrial thrombi before the surgical and EP procedure and before hospital discharge for patients in protocols 2 and 3. RESULTS: In group 1 (n = 20), 1 patient (5%) had a postoperative stroke with persistent neurologic deficit, and 6 other patients (30%) had a new thrombus in the left atrial appendage seen on the pre-EP TEE. In group 2 (n = 6), 3 left atrial appendage thrombi occurred (50%; 2 on predischarge TEE and 1 on pre-EP TEE). In group 3 (n = 26), no intracardiac thrombi were found on predischarge and pre-EP TEE, and there were no strokes in this group of patients, namely, the rates of thrombus or stroke were significantly reduced when compared with groups 1 and 2 (p = 0.001). CONCLUSIONS: Thoracoscopic ablation of AF can be associated with a risk of left atrial appendage thrombus formation and possibly also stroke. With administration of heparin during the ablation, followed by occlusion of the left atrial appendage as a part of the procedure, this risk can be effectively reduced.
Keywords: Thrombosis; Heparin; Thoracoscopy; Male; Risk Factors; antikoagulancia; následné studie; Česká republika; cévní mozková příhoda; Adult; Stroke; Aged; dospělí; mužské pohlaví; senioři; incidence; Catheter Ablation; trombóza; Follow-Up Studies; Atrial Fibrillation; Czech Republic; lidé; ženské pohlaví; Anticoagulants; Humans; síňové ouško; rizikové faktory; torakoskopie; Atrial Appendage; katetrizační ablace; Female; heparin; lidé středního věku; Incidence; fibrilace síní; Middle Aged